Technologija optimizacii ritma trojnogo pryžka v techniceskoj podgotovke legkoatletov-prygunov - Ogandžanov, A. L.; Salamatov, M. B.; Chaljutina, E. N. (Vestnik sportivnoj nauki; Sports science bulletin, 2018)
Optimization of balance of length in basic and flight phases is one of the key moments of improvement in a triple jump technology. This research is devoted to development of methodic of control and improvement of a triple jump rhythm on the basisof using electron beam device "OptoJump Next". Optimal parameters of the jump are justified. It is shown that if the individualrhythmic structure of the athlete`s triple jump does not match the model indicators, an operational correction of the technicaltraining in two stages is necessary. At the first stage, an analysis of the individual structure of special physical preparedness is made on the basis of the assessment methodology and model characteristics, certain motor abilities that predominate in the given athlete ("high-speed" or "power" type) are singled out, or their relatively uniform development ("universal"). In the second stage, jumpers are invited, with the help of special exercises and remote control equipment for technical training, to adjust the rhythm of the triple jump support and flight phases and bring it into line with the individual structure of the athlete`s special physical fitness based on the developed recommendations